2008
DOI: 10.1055/s-2007-1024457
|View full text |Cite
|
Sign up to set email alerts
|

Neurokardiogene Synkopen bei Herzschrittmachertherapie

Abstract: Patients with syncope while sitting or standing should undergo the tilting table test to determine whether the cause is neurocardiogenic so that pacemaker implantation can be avoided. The majority of patients with NS can be successfully treated by drugs. But in some patients pacemaker implantation may have to considered if drug treatment has failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Keim et al. [18] reported a series of eight patients with pacemaker and recurrent syncope. In all patients, the tilt test was positive with 50% pure vasodepressor, 38% mixed and 12% cardioinhibitory responses, thus with a distribution of positive tests being somewhat similar to our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keim et al. [18] reported a series of eight patients with pacemaker and recurrent syncope. In all patients, the tilt test was positive with 50% pure vasodepressor, 38% mixed and 12% cardioinhibitory responses, thus with a distribution of positive tests being somewhat similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested value of performing HUT in the evaluation of patients with PM and recurrent syncope [15] , [17] , [18] , [20] . In the INVASY and VASIS studies [7] , [10] , HUT preformed after PM implantation in a fraction of patients was not a predictor of clinical recurrence.…”
Section: Discussionmentioning
confidence: 99%